Case Report: Multicentric Reticulohistiocytosis Associated With Posterior Mediastinal Adenosquamous Carcinoma, Antinuclear Antibody Positivity and Lupus Anticoagulant Positivity - Tang, Ziyi; Wang, Xiangpeng; Xia, Zijing; Wang, Zhongming; Zhao, Yi; Liu, Yi (Frontiers in Immunology, 2022)
Multicentric reticulohistiocytosis (MRH) is a rare systemic disease of non-Langerhans cell histiocytosis. A number of studies in the literature have documented that it can coexist with malignancy or autoimmune disease, making it difficult to determine the most appropriate therapy. Here, we present a case study of MRH associated with posterior mediastinal adenosquamous carcinoma along with antinuclear antibody positivity and lupus anticoagulant positivity. The patient experienced 6 months of clinical benefit after surgical resection and chemoradiotherapy of the mediastinal malignancy. This case adds to the available literature on multicentric reticulohistiocytosis associated with different types of malignancy and provides supplementary clinical data on the coexistence of this syndrome with malignancy and immune system abnormalities. To the best of our knowledge, this is the first case study describing MRH accompanied by posterior mediastinal adenosquamous carcinoma and lupus anticoagulant positivity. The unknown aetiology and polymorphic clinical presentation of MRH warrants further investigation.